Predisposing, Enabling and Reinforcing Factors Associated with Sexual Intercourse Intention among Indonesian Young Men - Mohammad Ainul Maruf; Kerry Richter; Amara Soonthorndada (Jurnal Kedokteran dan Kesehatan, 2021)
Premarital sex among young men is more acceptable than young women. The Indonesian Demographic and Health Survey data consistently shows that the percentage of sexual experiences in young men is higher than that of young women and is increasing every year (6% versus 1% in 2007 and 8% versus less than 1% in 2012). This study aims to investigate which factors influence sexual intercourse intention among young men in Indonesia. This study obtained data from the 2012 Indonesian Demographic and Health Survey, especially the Adolescent Reproductive Health component with a total number of respondents of 9,109 young unmarried men. Data were analyzed descriptively and inferentially using the chi-square test and the Mann Whitney test. There are 21.1% of young men who intend to have premarital sex. Predisposing factors such as knowledge and attitudes on reproductive health, enabling factors such as dating behavior, as well as reinforcing factors such as sources of reproductive health information (peers, siblings/relatives, health service providers, religious leaders and the media) were found to be associated with the intention to have sexual intercourse. These findings indicated the need to strengthen the role of peer educators and health service providers as well as the involvement of religious leaders, and the media in adolescent reproductive health programs.